(untitled) (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2023)
Increasingly, the current business environment is requiring more real-time, scaled and fault tolerant application designs with the ability to accommodate large volume event in distributed cloud environments. Monolithic and request-based systems have been found to have issues with latency, lack of scalability and resilience when it comes to working with ever-generated enterprise data. The study introduces an Event-Driven Enterprise Application Framework that is based on an Apache Kafka and a Resilient Cloud-Native Architecture to facilitate the processing of events in a reliable, asynchronous and intelligent manner. The suggested framework is a combination of event producers, Apache Kafka clusters, distributed message topics, stream processing engines, microservices, API gateways, Kubernetes-based container orchestration, service mesh, cloud-native databases, distributed caching, observability services, and automated recovery mechanisms. The architecture uses event sourcing, Command Query Responsibility Segregation (CQRS), schema management, fault tolerance, horizontal auto-scaling, and AI-assisted monitoring to enhance the responsiveness of the system, its operational reliability, and resource usage. Cloud-native technologies provide dynamic workload management, self-healing deployments, continuous integration and continuous deployment (CI/CD) and secure communication between distributed services. Additionally, full-scale monitoring, distributed tracing, and predictive analytics allows detecting anomalies and optimization of performance proactively. The proposed architecture provides a versatile and strong foundation of enterprise applications utilized in the domain of finance and healthcare, retail, manufacturing, logistics, and IoT ecosystems in cases when low-latency event processing and high system availability are essential. The framework illustrates how the event-driven principles and cloud-native resiliency can contribute greatly to the agility of the enterprise, operational efficiency, fault tolerance, and business continuity as part of the contemporary digital transformation initiatives.